Obstetric Characteristics and Functional Outcomes in Women with Obstetric Anal Sphincter Injury - Adhikari, Shree Prasad; Poudel, Sandesh; Baidhya, Sapana Amatya; Yadav, Manisha (Journal of Nepal Health Research Council, 2024)
Background: Obstetric anal sphincter injury is a complication of vaginal delivery, if left untreated, causes significant maternal morbidities; urinary problems and fecal/ flatus incontinence. The aim of this study was to determine the incidence and describe the obstetric characteristics and functional outcomes of women who had vaginal delivery at Paropakar Maternity and Women’s Hospital Nepal and sustained Obstetric anal sphincter injury. Methods: This retrospective descriptive study included women who had vaginal delivery, irrespective of parity, in the labor room or birthing unit of Paropakar Maternity and Women’s Hospital from April 2018 to September 2020, and sustained Grade III or IV Obstetric anal sphincter injury after 28 weeks period of gestation. Maternal characteristics, obstetric details and perineal status after vaginal delivery were noted after review of hospital records. The patients were further inquired via telephone for their current status of fecal and/or urinary incontinence. Results: The incidence of OASI was 106 (0.33%) among 31, 786 Nepalese women with vaginal birth over a 2-year period. The mean age women with Obstetric anal sphincter injury was 24.6 ± 4.3 years and 45(52.9%) cases belonged to Janajati ethnicity. Fifty two (61.2 %) were primipara and 77 (90.6%) had spontaneous vaginal deliveries. Episiotomy was not performed on most of the patients (63, 74.1%). Problems with flatus holding, stool holding and urine holding was reported by 28.3%, 13.2% and 22.6% women respectively.Conclusions: The incidence of Obstetric anal sphincter injury among Nepalese women with vaginal birth over a 2-year period was 0.33%, which was lower than other South Asian studies. Grade III Obstetric anal sphincter injury was the frequent most type. The injuries were more common in women with Janajati ethnicity, primipara and women who did not have episiotomy. Problems with flatus holding and urine holding were present in almost one-fourth of the women with Obstetric anal sphincter injury at follow up.Keywords: Augmentation; episiotomy; induction; obstetric anal sphincter injury.